Influence of different protein supplements on the recovery and in vitro maturation of bovine oocytes - Fernandes-França, Pedro H.; Oliveira-Santos, Maria V.; Oliveira-Lira, Gabriela P.; Azevedo-Borges, Alana; Fernandes-Pereira, Alexsandra (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Oocyte quality and maturation are influenced by protein supplementation. Objective: To evaluate the influence of fetal bovine serum (FBS) and bovine serum albumin (BSA) concentrations on the recovery and in vitro maturation (IVM) of bovine oocytes. Methods: The study was divided into Stage 1 (oocyte recovery), and Stage 2 (IVM). In the first stage, three experiments were conducted according to the recovery (R) medium used: (R1) 10 vs. 20% FBS; (R2) 5 vs. 10% BSA; and (R3) the best results from R1, R2, and the combination of FBS+BSA (5+5%). Within the second stage, the maturation medium was supplemented according to three experiments: (M1) 5 vs. 10% FBS; (M2) 0.4 vs. 0.8% BSA; and (M3) better results of M1, M2, and the combination of FBS+BSA (5+0.8%). Results: In Stage 1 (R1 and R2), the media with 10% FBS and 10% BSA showed better oocyte quality results and were defined for experiment R3. In R3, the 10% FBS and the combination of FBS+BSA (5+5%) allowed recovery of better-quality oocytes. In Stage 2 (M1 and M2), media with both levels of FBS (5 and 10%) and 0.8% BSA were defined as better according to the maturation and viability rates of cumulus cells, so they were defined for experiment M3. In M3, no difference was noted among the supplements. Conclusions: For oocyte recovery, 10% FBS and the combination of FBS+BSA (5+5%) can be used to obtain immature oocytes. For the in vitro maturation, FBS (both levels, 5 and 10%) and BSA (0.8%) can be used alone or in combination.